Probes of the Mitochondrial cAMP-dependent Protein Kinase - Shell, Jennifer R. (2013)
The development of a fluorescent assay to detect activity of the mitochondrial cAMP-dependent protein kinase (PKA) is described. A peptide-based sensor was utilized to quantify the relative amount of PKA activity present in each compartment of the mitochondria (the outer membrane, the intermembrane space, and the matrix). In the process of validating this assay, we discovered that PKA activity is regulated by the protease calpain. Upon exposure of bovine heart mitochondria to digitonin, Ca(2+), and a variety of electron transport chain inhibitors, the regulatory subunits of the PKA holoenzyme (R(2)C(2)) are digested, releasing active catalytic subunits. This proteolysis is attenuated by calpain inhibitor I (ALLN).